Influence of dexamethasone and surfactant in the vitality and lung function of preterm lambs born by cesarean section - Bovino, F. [UNESP]; Denadai, D. S. [UNESP]; ávila, L. G. [UNESP]; Deschk, M. [UNESP]; Santos, P. S.P. [UNESP]; Feitosa, F. L.F. [UNESP]; Peiró, J. R. [UNESP]; Mendes, L. C.N. [UNESP] (FapUNIFESP (SciELO), 2019)
The aim of this study was to assess the vitality and lung function of preterm lambs. Twenty seven preterm lambs were divided in four groups. Group I (n=6) preterm lambs/ control; group II (n=9) lambs born to mothers that were treated with dexamethasone antepartum; group III (n=6) lambs treated with surfactant; and group IV (n=6) lambs treated with surfactant and born to mothers that were treated with dexamethasone antepartum. The APGAR score was performed after birth (T 0 ) and 15 minutes later (T 1/4 ) to assess vitality. The vital signs, blood gas analysis, spirometry and capnometry were assessed immediately after birth and continued until 48 hours. Chest radiographs were performed at T 0 , T 24 and T 48 . Significant rectal temperature interactions occurred at T 1 and T 6 depending on the type of treatment used. All animals showed low pH values, which were associated with high pCO 2 values and HCO 3 -values that increased over time from immediately after birth to two days of age. Higher tidal volume values were observed at T 1/4 , T 1 and T 24 when the animals were not treated with surfactant. Capnometry showed significant interactions between treatments at T 0 . Premature animals showed low vitality and impaired pulmonary function.

O objetivo do presente trabalho foi avaliar a vitalidade e a função pulmonar de cordeiros prematuros. Vinte e sete cordeiros foram divididos em quatro grupos: grupo I (n= 6), cordeiros prematuros/controle; grupo II (n= 9), cordeiros prematuros nascidos de mães tratadas com dexametasona antes do parto; grupo III (n= 6), cordeiros prematuros tratados com surfactante; e grupo IV (n= 6), cordeiros prematuros tratados com surfactante e nascidos de mães tratadas com dexametasona antes do parto. O escore APGAR foi realizado após o nascimento (T 0 ) e 15 minutos depois (T 1/4 ). Os parâmetros vitais, hemogasometria, espirometria e capnometria foram avaliados após o nascimento até 48 horas. As radiografias torácicas foram realizadas em T 0 , T 24 e T 48 . Interações significativas de temperatura retal ocorreram em T 1 e T 6 , dependendo do tipo de tratamento utilizado. Todos os animais apresentaram valores de pH baixos, que foram associados com altos valores de pCO 2 e valores de HCO 3 que aumentaram ao longo do tempo. Os maiores valores de volume corrente foram observados em T 1/4 , T 1 e T 24 , quando os animais não foram tratados com surfactante. A capnometria mostrou interações significativas entre tratamentos em T 0 . Os animais prematuros apresentaram pouca vitalidade e deficiência da função pulmonar.
Keywords: Cordeiro; Lambs; Neonatologia; Neonatology; Parâmetros vitais; Vital parameters; Vitalidade; Vitality